FACTORS AFFECTING TAX AGGRESSIVENESS IN COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Veronica, Francia; Christian, Natalis (KEUNIS, 2024)
This research use quantitative research methods that examines the impact of board independence, gender diversity, managerial ownership, institutional ownership, and ownership concentration on tax aggressiveness. It also investigates how audit quality moderates the relationship between these variables and tax aggressiveness. The research, based on a purposive sample of 566 companies from audited financial reports on the Indonesia Stock Exchange (BEI) spanning 2018 to 2022, uses panel regression with EViews version 12. Findings indicate that board independence, gender diversity, and ownership concentration do not significantly affect tax aggressiveness, while managerial and institutional ownership have a noteworthy impact. Ineffective implementation of independent commissioners' roles, male dominance in management, and the lack of expected theoretical impact on overseeing management do not influence tax aggressiveness. The research also shows that audit quality as moderating variable does not significantly moderate the relationship between these variables and tax aggressiveness.